(PSIV-18) Standardized Ileal Digestible Amino Acids and Digestible Energy Contents in Two Modified Soy Protein Concentrates and Soybean Meal Fed to Growing Pigs. (12th April 2022) - Huber, Lee-Anne; Zhu, Cuilan; Hansen, Lauren; Kozole, Cierra; Alfonso, Cristhiam Jhoseph Munoz; Mark, Jessica; Kakhki, Reza Akbari Moghaddam; Rho, Youngji; Kiarie, Elijah
Abstract: Six ileal-cannulated barrows (28.0±1.3 kg initial BW) were used in an incomplete Latin square design over four periods (n=7 or 6) to determine standardized ileal digestible (SID) AA and digestible energy of two modified soy protein concentrates [MSPC1 and MSPC2] and soybean meal (SBM). Pigs were fed one of three cornstarch-based diets with either MSPC1 or MSPC2 or SBM as the sole source of AA at a rate of 2.8 × estimated maintenance energy requirement. In each period, pigs were adapted to diets for 7 days followed by 2 days of fecal collection and subsequently, 2 days of continuous ileal digesta collection for 8 hours. The SID of AA were calculated using basal endogenous losses from a previous study for pigs fed a nitrogen-free diet. The digestible energy of the ingredients was calculated according to the difference method using the nitrogen-free diet that contained the same cornstarch:sucrose:oil ratio as the three test diets. The SID of crude protein was greater for MSPC1 (96.9%) than for SBM (91.3%; P < 0.05), while an intermediate value was observed for MSPC2 (94.3±1.2%). The SID of Ile, Leu, Lys (93.9%), Phe, and Val were not different between MSPC1 and MSPC2 but greater than for SBM (SID Lys: 84.5±1.7%; P < 0.05). The SID of His, Met, and Thr were greater for MSPC1 than MSPC2 and SBM (P < 0.05), which were not different. The SID of Arg was greater for MSPC1 than MSPC2 and SBM (P < 0.05), and greater for MSPC2 than SBM (P < 0.05). The digestible energy was greater for MSPC1 (4, 677 kcal/kg) than MSPC2 and SBM (3, 896±239 kcal/kg; P < 0.05), which were not different. Therefore, the MSPC1 was a better source of SID AA and digestible energy than either MSPC2 or SBM and could be used as a high-quality protein ingredient in swine rations.